Motivations and deterrents of blood donation among blood donors during the COVID‐19 pandemic in Hong Kong - Judy Yuen‐man Siu; Engle Angela Chan; Angus Siu‐cheong Li; Yik Mun Lee (Wiley, 2022)
Abstract Background The COVID‐19 pandemic has resulted in a reduction in blood donations and limited blood supply in many countries. The theory of planned behaviour has been widely used in past studies to understand the factors influencing blood donation. However, this theory limits analyses to the individual level. Furthermore, most research on the determinants of blood donation during the COVID‐19 pandemic is quantitative in nature, with relevant qualitative research being rare. Objectives To investigate the motivators and demotivators for donating blood among current blood donors during COVID‐19 pandemic. Design Forty in‐depth, individual semistructured interviews were conducted with current blood donors from December 2020 to March 2021 in Hong Kong. Thematic content analysis was adopted in the data analysis. Results The majority of the participants (n = 37) were demotivated from donating blood during the COVID‐19 pandemic. Factors at the perceptual, social and institutional levels interacted to cause this reluctance. Only three participants felt more motivated to donate blood. The data revealed that sociocultural forces and government pandemic prevention policies strongly affected the participants' motivations to donate blood during the pandemic. Conclusion This study presents a macro understanding of blood donation behaviour by investigating the institutional, social and perceptual factors influencing current blood donors during the COVID‐19 pandemic. This adds a more comprehensive understanding of blood donation where the theory of planned behaviour is widely used in past studies. Public Contribution The participants shared their experiences in the interviews. Their experiences provide hints for explaining the decreasing blood donation during the pandemic times.